Internet connectivity disruption in Croatia (Croatia) - Voidly (2026)
CRITICAL severity disruption detected in Croatia. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: HR-2026-0005
Keywords: internet disruption; HR; disruption; critical